Letter (copy) : Ray Cox Memorial - Citrine, Walter, 1887-1983
042-0068-001 WMC/WJB/MS/306 International 7th February, 1938. Mr. G. Stolz. International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, VIIe. Dear Comrade Stolz, RAY COX MEMORIAL. Thank you for your letter of the 4th instant notifying the further steps you have taken in order to obtain the promised photograph of this memorial. We are sending a copy of your communication to the Southampton Trades Council. Yours faithfully, General Secretary, 292/946/42/68